2011
DOI: 10.1177/000348941112000301
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Steady-State Electrical Stimulation of the Vestibular System in Humans

Abstract: Objectives. Efforts towards the development of a vestibular implant are being made. To mimic the physiology of the vestibular system, such a device must be first capable to restore a baseline or "rest" activity in the vestibular pathways and then to modulate it according to direction and velocity of head movements. The aim of this study was to assess whether a human subject could adapt to continuous electrical stimulation of the vestibular system, and if it was possible to elicit artificially oscillatory smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(125 citation statements)
references
References 16 publications
3
110
0
8
Order By: Relevance
“…This duration may be shortened by exposing subjects to multiple on/off cycles (Merfeld et al 2006;Lewis et al 2010). Initial studies in humans suggest that they may adapt more quickly than do monkeys: Guyot et al recently reported that a human receiving prosthetic vestibular stimulation adapted to a null in "spontaneous" nystagmus by ∼27 min during the first off→on cycle and in less than 5 min after several cycles (Guyot et al 2011a). …”
Section: Transitioning To Human Vestibular Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This duration may be shortened by exposing subjects to multiple on/off cycles (Merfeld et al 2006;Lewis et al 2010). Initial studies in humans suggest that they may adapt more quickly than do monkeys: Guyot et al recently reported that a human receiving prosthetic vestibular stimulation adapted to a null in "spontaneous" nystagmus by ∼27 min during the first off→on cycle and in less than 5 min after several cycles (Guyot et al 2011a). …”
Section: Transitioning To Human Vestibular Stimulationmentioning
confidence: 99%
“…By delivering biphasic, symmetric, charge-balanced, rate-modulated pulses, the device generated partly compensatory eye movements for head rotations about the gyro's axis of rotational sensitivity. Wall, Guyot, and colleagues have applied a similar approach to single-channel vestibular nerve stimulation in humans (Wall et al 2007;Guyot et al 2011aGuyot et al , b, 2012, and Nie, Phillips, Rubinstein, and colleagues have recently applied analogous technology to monkeys and a human subject as part of an effort to develop a vestibular pacing device for treatment of Ménière's disease (Nie et al 2011;Rubinstein et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…First, the patient received steadystate electrical stimulation in order to restore an artificial "spontaneous" firing rate in his deafferented vestibular nerve until nystagmic responses vanished 6 . Once the patient was in this "adapted state", we patient's eye movements were recorded while the patient was submitted to whole body rotations in the horizontal plane (sinusoidal 30 °/s peak angular velocity at 1Hz and 2Hz) in complete darkness.…”
mentioning
confidence: 99%
“…The intralabyrinthine approach utilizing the osseous canal lumen to guide the electrode to the ampullae was originally pioneered by Suzuki and Cohen. 3 The other approach is extralabyrinthine and has been utilized for human studies performed by the Geneva group. 9,10 The extralabyrinthine approach has two components using transmeatal approach. The posterior ampullary nerve is reached via a transmeatal approach after drilling the floor of the round window niche.…”
Section: Surgery For Vestibular Implantmentioning
confidence: 99%